COT-9 Prognostic impact of hypercoagulation in glioblastoma and molecular mechanism thereof. (6th December 2021) - Negoto, Tetsuya; Komaki, Satoru; Moritsubo, Mayuko; Furuta, Takuya; Nakamura, Hideo; Morioka, Motohiro
Abstract: Introduction: Pathological features of glioblastoma include intravascular thrombosis, suggesting that the thrombus formation in tumor microenvironment contributes to progression of gliomas. Meanwhile, glioblastoma has been known to be high risk malignant tumor for venous thromboembolism, however, it remains unclear how the coagulation-fibrinolysis system is disrupted, which essentially grow within the cranium in a localized manner, and how the disruption contributes to the malignant transformation. Methods: Total 64 patients with glioblastoma between January 2014 and April 2021 who underwent a D-dimer test before the therapeutic intervention were divided into two groups: the high D-dimer group (D-dimer level >3.0μg/ml) and the low D-dimer group (D-dimer level <3.0μg/ml). We compared the two groups in the maximum gadolinium-enhanced MRI lesions, MIB-1 index, and gene abnormalities (IDH mutation, TERT promoter mutation, and MGMT promotor methylation). The progression-free survival (PFS) and overall survival were analyzed using the Kaplan-Meier method. Furthermore, in 23 patients who underwent a D-dimer test at recurrence, the time to death after recurrence was analyzed. Results: The PFS in high D-dimer group was significantly shorter than that in the low D-dimer group (log-rank p = 0.0075). The D-dimer increase at the time of recurrence significantly correlated with the decrease in post-recurrence survival duration (log-rank p = 0.0226). Moreover, the gadolinium-enhanced lesions in the high D-dimer group were significantly larger. Conclusion: The Pre-intervention D-dimer levels and PFS suggest that glioblastoma-induced systemic enhancement of the coagulation-fibrinolysis system plays a role in the malignant transformation. The D-dimer increase during the treatment was found to be a predictor of poor prognosis after recurrence. Furthermore, the MRI findings revealed a correlation between the D-dimer increase and the size of intratumoral necrosis. Meanwhile, no correlation with the MIB-1 index was found, suggesting that the mechanism of malignant transformation by hypercoagulation differ from enhanced cell proliferation.